PENGARUH DEVIDEN PAYOUT RATIO, LEVERAGE, DAN SUKU BUNGA TERHADAP BETA SAHAM - Soraya, Elly; Lutfiati, Anis (Kinerja, 2020)
This study aims to determine the effect of Dividend Payout Ratio (DPR), Leverage, and Interest Rates on Stock Beta in stocks listed on the Jakarta Islamic Index for the 2013-2019 period. The object of this research is the stocks that are consecutively included in the top 30 during the 2013-2019 period and always publish annual financial reports, namely 10 companies that are sampled. The results of this study indicate that simultaneously the dividend payout ratio (DPR), Leverage, and Interest Rate variables have a significant effect on Stock Beta. Partially Payout Ratio (DPR), Leverage, and Interest Rate have a significant effect on Stock Beta. The coefficient of determination (R Square), Dividend Payout Ratio (DPR), Leverage, and Interest Rate on Stock Beta is 41%. This shows that the Dividend Payout Ratio (DPR), Leverage, and Interest Rate can explain 41% of Stock Beta, while the remaining 59% is influenced by other factors.